Reconstructing Qur’anic Social Ethics: A Double-Movement Hermeneutical Reading of Q.S. al-Ḥujurāt: 10–13 - Zahiratun Hasanah; Muhyidin Azmi; Siti Maryam (Lembaga Yasin AlSys, 2026)
Although Qur’anic social ethics has been widely discussed, systematic contextualization of the ethical principles embedded in Qs. al-Hujurat verses 10–13 through Fazlur Rahman’s double movement theory remains limited. This study aims to identify the moral principles of social ethics contained in these verses and contextualize them within contemporary social life. Employing qualitative library research and contextual hermeneutics, the study analyzed the Qur’anic text, relevant commentaries, Fazlur Rahman’s writings, and related scholarly literature. Data were collected through systematic documentation, source selection, critical reading, thematic classification, and comparative interpretation. The first movement reconstructed the micro- and macro-historical contexts of revelation to identify the underlying moral concerns and formulate universal ethical principles, while the second movement applied these principles to contemporary challenges, including interpersonal conflict, derogatory speech, prejudice, privacy violations, discrimination, misinformation, and disrespect in educational and digital environments. The findings demonstrate that Qs. al-Hujurat verses 10–13 establish an integrated framework of social ethics grounded in brotherhood, reconciliation, human dignity, responsible communication, protection of honor, peaceful conflict resolution, and recognition of diversity. The verses prohibit mockery, insulting labels, negative suspicion, fault-finding, surveillance, and backbiting while grounding human dignity in piety rather than ethnicity, social status, or group identity. Their contextualization further provides practical ethical guidance for verifying information, protecting privacy, communicating respectfully, rejecting identity-based superiority, and cultivating humility and mutual respect among students, teachers, families, and wider communities. This study concludes that Qur’anic social ethics should extend beyond normative discourse into educational practice and digital citizenship. It contributes a contextual framework for translating Qur’anic moral principles into inclusive, peaceful, and ethically responsible social relations across contemporary educational and societal contexts.